Clutch size and egg repeatability in three elusive bird species: Little Bittern (Ixobrychus minutus), Little Crake (Zapornia parva) and Water Rail (Rallus aquaticus) from north-west Romanian populations - DAVID, Alin; STERMIN, Alexandru Nicolae; SEVIANU, Eliana (Studia Universitatis Babeș-Bolyai Biologia, 2018)
Data were collected from Little Bittern, Water Rail and Little Crake nests located in North-Western Romania, between April and July of 2002 - 2006 and 2010 - 2012. The repeatability was calculated as intra-class correlation of length, breadth and egg volume coefficients. The total number of active nests considered for the present study was as follows: 43 for Little Bittern, 25 for Water Rail and 9 for Little Crake. The clutch size in Little Bittern ranged from 4 to 7 eggs, in Water Rail from 4 to 10 and in Little Crake from 4 to 8 eggs. The repeatability values of egg parameters varied between 0.844 to 0.860 in Little Bittern, 0.262 - 0.374 in Water Rail and 0.310 - 0.574 in Little Crake. Short-term environmental impact was strong in case of Water Rail and Little Cracke, while the genetic component had little influence. For these two species, the low repeatability could be explained by larger numbers of eggs in a clutch, reflecting in turn a longer laying period.